Financial risk management by Malaysian life insurers: the application of reinsurance / Rosmi Yuhasni Mohamed Yusuf, Saharani Abdul Rashid and Rozain Daud - Mohamed Yusuf, Rosmi Yuhasni; Abdul Rashid, Saharani; Daud, Rozain (Institute of Research, Development and Commercialization (IRDC), 2005)
This research examines the determinants of reinsurance use as a tool for financial risk management in the Malaysian life insurance industry. We estimate a multivariate linear regression model using a sample of /7 Malaysian life insurers for the period between the years 2000 to 2003 with data taken from the Annual Insurance Report published by the Bank Negara Malaysia and Life Insurance Revenue Account of the respective insurer. Our results indicate that determinants of reinsurance used are negatively influenced by a firm's leverage and the availability of cash but positively influenced by bank affiliation relationship. This research however fails to find evidence that reinsurance decision is influenced by factors such as a firm size, profitability, taxes and group memberships. We conclude that reinsurance is still being applied in Malaysia as a pure risk spreading or risk transfer tool with minimal role in managing the financial risk in the Malaysian life insurance industry.